Regulation of medical activity in Russia and Europe in the 10th – early 20th centuries: correlation between ethical and legal principles - Valery V. Suvorov; Yuri V. Ishchenko; Elmira R. Fakhrudinova; Anton R. Kiselev (Russian Open Medical Journal)
The legal and ethical regulation of medical activity in Russia vs. European countries has common features and a number of specific differences. The regulation of medical activity in the Old Russian state and European medieval states was carried out within the framework of legal norms and Christian worldview, the main principle of which was service to one’s neighbor. For instance, these were ethical issues that came to the fore. The secular state form, began its historical path with the emergence of the first secular doctors at the courts of ancient Russian princes. From the 16th century on, it became part of the state apparatus extending its influence to the social estate of the military servicemen. In the middle of the 19th century, during the period of the Zemstvo Reform, it became the main form of servicing rural population. The specificity of zemstvo medicine was the organization of medical activities based on of local self-government bodies and medical societies. At the beginning of the 19th century, with the increasing complexity of scientific knowledge and organization of medical services, European medical codes of ethics aimed at developing the rules of conduct to be followed by the members of newly emerging national medical associations. Despite regulating medical activity, the issues of healthcare were not given due attention, and there were no specific legislative acts affecting the health care regulation in prerevolutionary Russia. In Europe, too, for a long time, the responsibility of a medical professional for mistakes was considered from the standpoint of private relationships based on contractual and commercial principles.